Modelling the low-frequency electrical properties of pyrite-bearing reservoir sandstones - Han, T.; Clennell, M.; Pervukhina, Marina (2015)
© 2015 Elsevier Ltd. Marine controlled source electromagnetic sounding has developed rapidly in recent years to complement conventional seismic method for better discrimination of pore fluid. To obtain quantitative and reliable interpretation of the CSEM data, a robust rock physics model is vital to link the bulk rock electrical conductivity to the electrical properties and microstructure of the rock constituents, especially when some of the constituents exhibit extreme electrical behaviours (e.g., pyrite, a common mineral associated with reservoir rocks). Based on the multi-phase incremental model validated on published experimentally measured electrical conductivity of pyrite-bearing sandstones, the effects of key parameters, i.e., pyrite content, porosity, pyrite conductivity, grain aspect ratio and water saturation on the electrical conductivity of pyrite-bearing sandstones and their corresponding CSEM responses were comprehensively studied. The results are expected to assist in the CSEM data interpretation when a pyrite-bearing sandstone reservoir is encountered in the future.